Pengaruh sistem administrasi pajak modern, kepuasan wajib pajak, penegakan sanksi pajak, dan keadilan distributif terhadap kepatuhan wajib pajak - Zulfa, Anis Azkiyah (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the impact of the modern tax administration system on taxpayer compliance at the Kantor Pelayanan Pajak Pratama Jakarta. A quantitative approach was used with a survey method targeting registered taxpayers. The results show that the use of modern tax technology, simplification of procedures, and improved services significantly influence taxpayer compliance. The study concludes that tax system modernization encourages higher tax compliance.